Dynamics of food intake and nutrition by expenditure class in India - Shariff, Abusaleh; Mallick, Ananta C. (1999)
In spite of early apprehensions, the foodgrain production in India has kept pace with population growth. Acute large-scale famines, which used to occur periodically before independence, have now been eliminated. In spite of this, a large proportion of poor households across India does not have access to adequate food due to lack of purchasing power. About 35 per cent or around 325 million Indians are classified as `poor'. Over 70 per cent of the family income in this category is spent to meet food and nutritional needs alone. The quinquennial consumer expenditure surveys of the NSSO make the estimation of the per capita intake of different food items and consequent supply of energy, proteins, fat, iron and calcium, possible. In this paper these estimates are presented at the all-India level according to expenditure class categories. According to this analysis food and nutrition deficiencies are much larger than what one would conceive by looking into poverty estimates. - Reproduced
Keywords: Nutrition